The association between the C-reactive protein-to-albumin-to-lymphocyte index and retinopathy: insights from a population-based study - Li, Pingping; Chen, Fangyu; Li, Lu; Wu, Jianhua (Frontiers in Nutrition, 2025)
IntroductionRetinopathy is a multifactorial disease influenced by metabolism, immunity, inflammation, and other factors. The C-reactive protein-albumin-lymphocyte (CALLY) index is a novel immunonutritional score that has shown promise in various health contexts. This study aims to investigate the association between the CALLY index and retinopathy risk, and to compare its predictive performance with other established inflammatory markers.MethodsData from 5,439 participants in the 2005–2008 National Health and Nutrition Examination Survey (NHANES) were utilized. Multivariable-weighted logistic regression was employed to assess the association between the CALLY index and retinopathy risk. Additionally, the predictive performance of the CALLY index was compared with other inflammatory markers. Mediation analysis was conducted to explore potential mediating factors in the association between the CALLY index and retinopathy.ResultsMultivariable-weighted logistic regression revealed a significant inverse association between the CALLY index and retinopathy risk (OR = 0.96, 95% CI = 0.94–0.98, P = 0.002). Participants in the highest CALLY index quartile exhibited a markedly lower risk of retinopathy (P < 0.001). The CALLY index demonstrated superior predictive performance compared to other inflammatory markers, with an area under the curve (AUC) of 0.672 (95% CI = 0.643–0.701). Mediation analysis indicated that high-density lipoprotein (HDL) levels partially mediated the association between the CALLY index and retinopathy.DiscussionThese findings highlight the CALLY index as a reliable, independent biomarker for retinopathy risk assessment, outperforming traditional inflammatory markers and oering potential clinical value for early identification of retinopathy in individuals with chronic diseases.